Can 3T MR Angiography Replace DSA for the Identification of Arteries Feeding Intracranial Meningiomas? - Uetani, H. (AJNR Am J Neuroradiol, 2013)
BACKGROUND AND PURPOSE: For identifying the arterial feeders of meningiomas, the usefulness of 3D TOF MRA at 3T has not been systematically investigated. This study was intended to assess whether unenhanced 3D TOF MRA at 3T can replace DSA for the identification of arteries feeding intracranial meningiomas and whether it is useful for assessing their dural attachment. MATERIALS AND METHODS: Twenty-one consecutive patients with intracranial meningiomas (18 women, 3 men; aged 42–77 years, mean 57 years) underwent DSA, conventional MR imaging, and 3D TOF MRA. Two neuroradiologists independently evaluated the primary and secondary feeders of each tumor on maximum-intensity-projection and source MRA images. They also identified the location of dural attachments based on information from MR imaging/MRA images. Interobserver and intermodality agreement was determined by calculating the κ coefficient. RESULTS: For the identification of primary and secondary feeders on MRA images, interobserver agreement was very good (κ = 0.83; 95% CI, 0.66–1.00) and moderate (κ = 0.58; 95% CI, 0.34–0.82) and intermodality agreement (consensus reading of MRA versus DSA findings) was excellent (κ = 0.94; 95% CI, 0.84–1.00) and good (κ = 0.72; 95% CI, 0.51–0.93), respectively. With respect to the dural attachment of meningiomas, interobserver agreement was very good (κ = 0.95; 95% CI, 0.84–1.00). The agreement in the diagnosis between MR imaging/MRA and surgery was excellent (κ = 1.00). CONCLUSIONS: Unenhanced 3D TOF MRA at 3T cannot at present supplant DSA for the identification of the feeding arteries of intracranial meningiomas. This information may be useful for evaluating their dural attachment.